STUDI LITERATUR : PENDEKATAN STRATEGIS DALAM PENGEMBANGAN KOGNITIF, AFEKTIF, DAN PSIKOMOTORIK SISWA DI SEKOLAH DASAR - Prayudi, Eko (Jurnal Sultra Elementary School, 2024)
Cognitive, affective, and psychomotor development are three key domains in education that complement each other. This article examines various strategic approaches to developing these three domains in elementary school students. A literature review was conducted by examining recent studies and relevant publications. The findings indicate that experience-based learning approaches, the use of innovative learning media, and holistic assessment are essential factors for successfully developing the cognitive, affective, and psychomotor abilities of students.